2021
DOI: 10.2478/oandhs-2021-0001
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of heavy metals in tilapia fish species and related histopathological changes in muscles, gills and liver of Oreochromis niloticus occurring in the area of Qahr El-Bahr, Lake Al-Manzalah, Egypt

Abstract: Accumulation of metals (Fe, Zn, Cu, Mn, Pb, Cd and Ni) in the muscles and gills of Oreochromis niloticus, Oreochromis aureus and Tilapia zillii was assessed based on seven locations in the Qahr El-Bahr area in Lake Al-Manzalah. The average accumulation of metals was in the following order: Tilapia zillii > Oreochromis aureus > Oreochromis niloticus. To determine the risk of fish consumption, the estimated daily intake, carcinogenic, non-carcinogenic and relative risk indices were calculated. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…The effects of lead might be attributed to its ability to generate reactive toxic action oxygen species. The Lead induce oxidative damage in several tissues by enhancing lipid peroxidation that occurs readily in the tissues, due to presence of membranes rich in polyunsaturated fatty acids (Mahmuda et al, 2020;Yacoub et al, 2021;Simukoko et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of lead might be attributed to its ability to generate reactive toxic action oxygen species. The Lead induce oxidative damage in several tissues by enhancing lipid peroxidation that occurs readily in the tissues, due to presence of membranes rich in polyunsaturated fatty acids (Mahmuda et al, 2020;Yacoub et al, 2021;Simukoko et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…They are typically regarded as the best species for determining how environmental changes affect organisms, and they are employed as bio-indicators to track water pollution in aquatic ecosystems (Kuklina et al, 2013). The exposure of fish in Lake Manzalah to diverse pollutants causes several pathological changes in the fish organs (Yacoub et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the MTs are able to form stable chelates with Pb The liver is the main metabolic organ, the amount of pollutants in fish liver is directly proportional to the degree of pollution in the aquatic environment (Yılmaz, 2009; Tapia et al, 2012). Many experimental and field studies showed that liver was the target organ for the accumulation of many metals and was highly active in the uptake and storage of metals because of its role in the storage, redistribution, detoxification, transformation of contaminants and the high induction rate of metallothioneins (MTs) in the liver (Dural et al, 2007;Yılmaz et al, 2010). In this context, liver has been recommended by many authors as the best environmental indicator of both the water pollution and chronic exposure to heavy metals (Agah et al, 2009;Messaoudi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%